The Importance Of The Ideas Of Jadidism In The Formation Of The Education System Of Turkestan - Bahritdin Samievich Turdiyev (Euro Asian Journal Publishing, 2024)
This article discusses processes related to the emergence of ideas of modernism in Turkestan in the late 19th - early 20th century, reform movements in the education system, as well as the historical significance of the modern educational movement in the analysis of cultural and educational life of the country.
Keywords: Turkestan land; contemporaries; intelligentsia of Turkestan